Using diffusion tractography to predict cortical connection strength and distance: a quantitative comparison with tracers in the monkey - Donahue, Chad J.; Sotiropoulos, Stamatios N.; Jbabdi, Saad; Hernandez-Fernandez, Moises; Behrens, Timothy E.; Dyrby, Tim B.; Coalson, Timothy; Kennedy, Henry; Knoblauch, Kenneth; Van Essen, David C.; Glasser, Matthew F. (Society for Neuroscience, 2016)
Tractography based on diffusion MRI offers the promise of characterizing many aspects of long-distance connectivity in the brain, but requires quantitative validation to assess its strengths and limitations. Here, we evaluate tractography's ability to estimate the presence and strength of connections between areas of macaque neocortex by comparing its results with published data from retrograde tracer injections. Probabilistic tractography was performed on high-quality postmortem diffusion imaging scans from two Old World monkey brains. Tractography connection weights were estimated using a fractional scaling method based on normalized streamline density. We found a correlation between log-transformed tractography and tracer connection weights of r = 0.59, twice that reported in a recent study on the macaque. Using a novel method to estimate interareal connection lengths from tractography streamlines, we regressed out the distance dependence of connection strength and found that the correlation between tractography and tracers remains positive, albeit substantially reduced. Altogether, these observations provide a valuable, data-driven perspective on both the strengths and limitations of tractography for analyzing interareal corticocortical connectivity in nonhuman primates and a framework for assessing future tractography methodological refinements objectively.